Hubungan Lama Penggunaan KB Suntik 3 Bulan terhadap Kejadian Amenorrhea pada Ibu di TPMB Domingas M.L.S.O Surabaya: The Relationship of Long-term Use of 3-month Injectable Contraceptives on the Occurrence of Amenorrhea in Mothers at the TPMB Domingas M.L.S.O Surabaya - Anastasya Suryaning Illah (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2022)
Injecting family planning users dominate in Indonesia, especially in the city of Surabaya in 2020 reaching 80%. Menstrual disorders are one of the side effects of using injectable contraceptives, especially 3-month injections. Menstrual disorders that are often complained of is amenorrhea. Amenorrhea is a condition in which women do not experience menstruation for at least 3 consecutive months. The purpose of this study was to determine whether there was a relationship between the duration of the use of 3-month injectable contraceptives on the incidence of amenorrhoea in mothers at TPMB Domingas M.L.SO Surabaya. This research method uses an analytical survey with a cross sectional approach. The population of this study were all acceptors of 3-month injection KB as many as 135 people. Obtained a sample of 100 people who meet the inclusion criteria. The sampling technique used the purposive sampling method. The independent variable is the duration of the use of injectable contraception for 3 months and the dependent variable is the incidence of amenorrhoea in the mother. Data analysis was performed using the chi-square test. The results showed that most users (68.3%) experienced amenorrhea. Statistical test showed that p = 0.000 (≤ 0.05). This means that there is a relationship between the duration of the use of 3 months injectable contraceptives and the incidence of amenorrhoea in mothers at TPMB Domingas M.L.S.O Surabaya. The conclusion in this study is that the longer you use the 3-month injectable contraception, the higher your risk of experiencing amenorrhea. It is recommended to the head of TPMB Domingas M.L.S.O Surabaya to continue to improve counseling and counseling to acceptors of 3-month injection KB regarding the long-term side effects of using 3-month injection KB.